Interrelated Values of Cultural Landscapes of Human Settlements: Case of Istanbul - Turkyilmaz, Cigdem Canbay (ELSEVIER SCIENCE BV, 2016)
With the rapid social and economic development, cultural landscapes are the most fragile and threatened sites on earth. This paper identifies interrelated values of cultural landscapes to preserve and requalify cultural landscapes. This value sets explore how the sense of place, cultural identity and heritage can become touchstones for the study on the transformation of cultural landscapes. In the scope of the study, cultural landscapes mean a cultural as well as historic property consists of all its cultural resources. This term can address not only an entire landscape but also a sculptural object, a landmark, or building. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: landscape; culture; transformation; Istanbul; MALAYSIA; Social Sciences - Other Topics